A new ferulic acid ester from Rhodiola wallichiana var. cholaensis (Crassulaceae). Issue 1 (2nd January 2018) - Song, Yaling; Zhou, Jianming; Wang, Xuejing; Xie, Xue; Zhao, Yiwu; Ni, Fuyong; Huang, Wenzhe; Wang, Zhenzhong; Xiao, Wei
Abstract: A new ferulic acid ester, 6-feruloyloxyhexanoic acid (1 ), was isolated along with 10 known ones (2 –11), from the concentrated water extract of Rhodiola wallichiana var . cholaensis. Their chemical structures were elucidated on the basis of extensive spectroscopic methods including Two-dimensional nuclear magnetic resonance (2D NMR) experiments. Compound3 was isolated from this plant for the first time. The protective effects against H2 O2 -induced myocardial cell injury in cultured H9c2 cells were also evaluated. Compounds1, 5 and7 –11 provided significant protective effects on H2 O2 -induced H9c2 cells injury at the concentration of 25 μg/mL. And the protective effects of compound1 was also investigated by the oxygen–glucose deprivation/reperfusion (OGD/R) tests. Abstract :